تأثير القدرة الإدارية في إستدامة الأرباح المحاسبية: بالتطبيق على عينة من شركات القطاع الصناعي المدرجة في سوق العراق للأوراق المالية (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims to measure the impact of managerial ability on income persistence for the industrial sector companies listed in the Iraqi Stock Exchange. The managers of these companies have managerial ability that may have an impact on achieving their objectives, setting their future policies and investing opportunities. Which may be reflected in many areas, including the level of profitability achieved and the possibility of continuity or sustainability? A model was used to measure managerial ability as well as a model to measure the income persistence in order to determine the relationship between them, The researchers found the absence of a statistically significant between managerial ability and the income persistence, which requires companies to attract executives with excellent managerial abilities Through the adoption of an appropriate mechanism in the field of recruitment, as well as strengthening the necessary procedures in the area of ​​ compensation and try to link the compensation to achieve the profits in a manner that motivates managers to maximize income and increase their Compensation and achieve the interests of the stakeholders.